Penerapan Literasi Oleh Mahasiswa Kampus Mengajar di Sekolah Dasar Melalui Kegiatan SeRaKa Bercerita - Kusamantha Dwi Kayanti; Nurul Wahida; Siska Dhia Pratiwi; Karina Lisia Nurzasmitha; Azalia Fikria (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The "SeRaKa Tells Stories" program (Tuesday, Wednesday, Thursday Tells Stories) is a form of service carried out in the Class 8 Teaching Campus Program to increase the literacy of elementary school students. This program aims to increase students' reading interest, storytelling skills, and reading comprehension through reading aloud methods, interactive discussions, and storytelling. Participants in this activity are students from SD Negeri 4 Ampenan three times a week. The results of the service showed a significant increase in students' interest in reading, their ability to understand reading content, and their confidence in speaking in public. Even though there are several obstacles, such as limited reading materials and limited time, this program still shows its effectiveness in building a sustainable literacy culture in elementary schools. Therefore, the development of creativity and technology-based literacy programs is recommended for further service to overcome challenges in increasing student literacy